2022
DOI: 10.3390/biomedicines10071666
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Stimulation for Lower Extremity Pain

Abstract: Peripheral nerve stimulation (PNS) is rapidly increasing in use. This interventional pain treatment modality involves modulating peripheral nerves for a variety of chronic pain conditions. This review evaluated its use specifically in the context of chronic lower extremity pain. Studies continue to elucidate the utility of PNS and better define indications, contraindications, as well as short- and long-term benefits of the procedure for the lower extremity. While large, prospective evidence is still lacking, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated a significant improvement in pain scores post-PNS implantation with a growing variety of implant locations being evaluated. This includes PNS therapy for low back pain, lower extremities, headaches, and even phantom limb pain [16][17][18][19][20][21]. In a retrospective study of 72 patients who underwent PNS therapy, pain scores and opioid utilization to manage pain improved within 6 months after implantation [22].…”
Section: Brief Summary and Published Data Comparisonmentioning
confidence: 99%
“…Several studies have demonstrated a significant improvement in pain scores post-PNS implantation with a growing variety of implant locations being evaluated. This includes PNS therapy for low back pain, lower extremities, headaches, and even phantom limb pain [16][17][18][19][20][21]. In a retrospective study of 72 patients who underwent PNS therapy, pain scores and opioid utilization to manage pain improved within 6 months after implantation [22].…”
Section: Brief Summary and Published Data Comparisonmentioning
confidence: 99%
“…Peripheral nerve injuries resulting from trauma or disease are often detrimental and can lead to chronic disabilities [ 3 ]. Patients with peripheral nerve injuries frequently suffer from sensorimotor deficits and neuropathic pain [ 4 , 5 ]. In addition to physical symptoms, patients with peripheral nerve injuries may also suffer from psychological symptoms, including depression and decreased self-efficacy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 This technique was much less invasive than previous procedures and was shown in the coming years to effectively treat many conditions such as lower back, groin, ankle, neck, and abdominal pain along with migraines and CRPS type 2. [15][16][17][18][19][20][21][22][23][24][25][26] This article presents a collection of cases comparing patient-reported pain scores before and after the implant at various sites of a percutaneous peripheral nerve stimulation lead/s with an external generator.…”
Section: Introductionmentioning
confidence: 99%